Low carbon energy supply technologies and systems - Sharma, Atul (Professor of environmental studies); Shukla, Amritanshu; Singh, Renu (CRC Press, 2020)
Future energy technologies must embrace and achieve sustainability by displacing fossil carbon-intensive energy consumption or capture/reuse/sequester fossil carbon. This book provides a deeper knowledge on individual low (and zero) carbon technologies in a comprehensive way, covering details of recent developments on these technologies in different countries. It also covers materials and processes involved in energy generation, transmission, distribution, storage, policies, and so forth, including solar electrical; thermal systems; energy from biomass and biofuels; energy transmission, distribution, and storage; and buildings using energy-efficient lighting.
Keywords: Renewable energy sources.; Carbon dioxide mitigation.; Energy development -- Environmental aspects.; elektronické knihy; electronic books